Linking Experiential Learning, Deep Learning Readiness, and School Well-Being in Indonesia: A Structural Equation Modeling Approach - Sutapa, Mada; Utari, Rahmania; Rahmawati, Tina; Pertiwi, Meilinda Chrisdian (Jurnal Akuntabilitas Manajemen Pendidikan, 2025)
This study investigates (1) the feasibility of a structural model using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and (2) the relationships among teachers’ experiences in implementing the Pancasila Student Profile (P5), their readiness to apply Deep Learning (DL), and efforts to achieve School Well-Being (SWB). The participants were 99 public and private elementary and junior high school teachers from the Special Region of Yogyakarta, Central Java, and East Java, selected through convenience sampling. Data were collected using a closed-ended questionnaire with a four-point Likert scale. The instrument was developed using a formative approach, with content validity assessed by two experts, while construct validity and reliability were examined through the SEM-PLS outer model. The results show that the proposed structural model demonstrates an excellent goodness of fit (SRMR = 0.048). The model explains DL Readiness at a weak-to-moderate level (R² = 0.245) and SWB at a very strong level (R² = 0.753). Teachers’ experience in implementing P5 has a significant positive effect on their readiness to apply DL. In turn, DL Readiness has a very strong and significant effect on efforts to achieve SWB. However, teachers’ P5 implementation experience does not have a direct significant effect on SWB. Further analysis confirms a significant indirect effect, indicating full mediation through DL Readiness. Effect size analysis reinforces these findings, highlighting DL Readiness as the dominant predictor of SWB. Overall, the study suggests that SWB is primarily shaped by teachers’ readiness to implement DL practices rather than by P5 implementation experience only.